The Notions “Integrative Orientation” and “Instrumental Orientation” and Their Extents of Relevance in Today’s ELT Motivational Studies: A Critical Analysis - Subekti, Adaninggar Septi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
This paper aims to give a critical analysis on the two prevailing notions introduced by Gardner and associates, Integrative Orientation and Instrumental Orientation, in today’s ELT researches. Dörnyei and associates argued that integrative and instrumental orientations are unable to capture learners’ fluctuations and complexity of motivation as the result of many factors from within learners and outside learners, who are also social beings in their respective environments. The two orientations also trigger misinterpretations among researchers as they are often used interchangeably with motivations while they are two very different concepts. Furthermore, the growing prominence of Global English perspective, which does not see L1 speakers of English as the standards of “correctness” and “good English” also contributes to growing irrelevance of the integrative orientation notion among researchers. Based on the critical analysis, it is suggested that researchers focus on qualitative approaches in investigating English learners’ motivation as the acknowledgement of its complexity and to limit greed to oversimplify and generalize motivation of learners, who are also social beings with all the complexity and dynamics. Keywords: Integrative orientation, instrumental orientation, motivation